Identification of disulfide cross-linked tau dimer responsible for tau propagation - Kim, Dohee (Sci Rep, 2015)
Recent evidence suggests that tau aggregates are not only neurotoxic, but also propagate in neurons acting as a seed for native tau aggregation. Prion-like tau transmission is now considered as an important pathogenic mechanism driving the progression of tau pathology in the brain. However, prion-like tau species have not been clearly characterized. To identify infectious tau conformers, here we prepared diverse tau aggregates and evaluated the effect on inducing intracellular tau-aggregation. Among tested, tau dimer containing P301L-mutation is identified as the most infectious form to induce tau pathology. Biochemical analysis reveals that P301L-tau dimer is covalently cross-linked with a disulfide bond. The relatively small and covalently cross-linked tau dimer induced tau pathology efficiently in primary neurons and also in tau-transgenic mice. So far, the importance of tau disulfide cross-linking has been overlooked in the study of tau pathology. Here our results suggested that tau disulfide cross-linking might play critical role in tau propagation by producing structurally stable and small tau conformers.